Using a panel of multiple tumor‐associated antigens to enhance the autoantibody detection in the immunodiagnosis of ovarian cancer. Issue 3 (28th November 2018) - Wang, Peng; Qin, Jiejie; Ye, Hua; Li, Liuxia; Wang, Xiao; Zhang, Jianying
Abstract: Background: Ovarian cancer (OC) is a major malignancy affecting a large population over the world, and a biomarker that holds diagnostic potential is of critical importance. Recently, autoantibodies have been indicated as biomarkers in multiple cancer research. The current study was designed to explore the practice of using autoantibodies in diagnostic settings by the enzyme‐linked immunosorbent assay of sera with a panel of tumor‐associated antigens (TAAs). Methods: A panel of 12 TAAs was selected to detect the corresponding autoantibodies in sera sampled from 132 OC patients as case group and 147 normal healthy individuals as the control group. The diagnostic potential of this panel was evaluated by conventional evaluation, receiver operating characteristic (ROC) curve analyses, and classification tree analysis. Results: When the cutoff values were set as mean ± 2 SD for normal healthy individuals, the positive rates of antibodies to any single TAA were less than 20% both in OC and in normal healthy individuals. In a parallel screening approach, a panel of nine TAAs (p53, C‐myc, p90, p62, AHSG, 14‐3‐3zeta, RalA, Koc, and p16), obtained optimal diagnostic performance in OC with the sensitivity of 61.4% at the 85.0% specificity. In addition, when the nine TAAs were combined with CA125, the sensitivity and specificity were improved to 94.7% and 78.2%, respectively. The ROC curve analyses showed that only the area under the receiver operating characteristic curves (AUCs) of antibodies against C‐myc, Koc, and RalA was beyond 0.6, which were 0.732, 0.668, and 0.665, respectively. The AUC of the combination was up to 0.914 ( P  < 0.05). Decision tree analysis showed that C‐myc, HCC1.3, RalA, and CA125 held high potential in the detection of OC. The panel of nine TAAs also identified 78.8% of OC patients who had normal CA125 levels in their serum samples, indicating that elevated CA125 and anti‐TAA antibodies appeared to be independent but supplementary biomarkers for diagnosing OC. Conclusions: In summary, the current study further supports that a customized TAA panel can serve as a promising and powerful tool for immunodiagnosis of OC and may be particularly useful in patients with normal CA125 levels. Abstract : In summary, the current study further suggested that a panel of tumor‐associated antigens (TAAs) could enhance antibody detection in immunodiagnosis of ovarian cancer (OC). The data in this study showed that TAAs panel might be a novel noninvasive approach to distinguish OC from normal individuals. We conclude that multiple anti‐TAAs antibody detections may improve the diagnostic value of OC.